Integrative Analysis of Minichromosome Maintenance Proteins and Their Prognostic Significance in Melanoma - Han, Wei; Wu, Yi-Zhu; Zhao, Xiao-Yu; Gong, Zhen-Hua; Shen, Guo-Liang (Frontiers in Oncology, 2021)
Background: Minichromosome maintenance (MCM) is known for participating in cell cycle progression as well as DNA replication. While the diverse expression patterns and prognostic values of MCMs in melanoma still remained unclear. Methods: In the present study, the transcriptional and clinical data of MCMs were explored in patients with melanoma from GEO, TCGA, ONCOMINE, GEPIA, UALCAN, cBioPortal, and TIMER databases. Results: We found that the elevated expression of MCM2-6 and MCM10 were significantly expressed in melanoma compared to normal skin. High mRNA level of MCM4, MCM5 and MCM10 were closely related to worse prognosis in patients with melanoma. GSEA analysis showed hallmark pathways were most involved in mTORC1 signaling, G2M checkpoint, E2F targets, and mitotic spindle. Furthermore, we found potential correlations between the MCMs expression and the immune cells infiltration, including B cells, CD4+ T cells, CD8+ T cells, neutrophils, macrophages, and dendritic cells. Conclusion: In conclusion, up-regulated MCMs gene expression in melanoma probably played a crucial part in the development and progression of melanoma. The up-regulated MCM4/5/10 expression were used as the potential prognostic markers to improve the poor outcome and prognostic accuracy in patients with melanoma. Our study might shed light on the selection of prognostic biomarkers as well as the underlying molecular pathogenesis of melanoma.